The Effect of Stretching Excercise as Complimentary Therapy on Blood Pressure in Patients with Hypertension in the Cibodasari Health Center Tangerang - Sarah Raudhatul Aulia; Ani Fadmawaty; Lindawati Lindawati (Journal of Noncommunicable Diseases Prevention and Control, 2023)
This study aims to determine the effect of complementary therapy stretching exercises on blood pressure in hypertension patients. This research uses a quantitative approach with a quasi-experiment design and a one-group pre-test and post-test design. The intervention provided was stretching exercises for 30 minutes twice a week in the morning and evening for 2 weeks, by measuring the blood pressure before and after the intervention. The number of samples taken was 15 respondents from a total population of 374 hypertension sufferers in the Cibodasari Community Health Center Tangerang, using a purposive sampling technique. Using the paired sample t-test for bivariate analysis, the average drop in respondents' systolic blood pressure was 6,133, from 151.20 (pre-test) to 145.07 (post-test), and the average drop in respondents' diastolic blood pressure was 7,333, from 89.20 (pre-test) to 81.87 (post-test). Based on the t-dependent statistical test, significant results were obtained with a p-value of 0.002 for systolic pressure and a p-value of 0.003 for diastolic pressure. The results of the study show that stretching exercises have an effect on reducing blood pressure in hypertension sufferers, which can be applied simultaneously with other pharmacological therapies.